Effects of Pilates in Reducing Depression, Anxiety, and Stress in Pregnant Women: A Systematic Review and Meta Analysis - Rifyal Syauqi Muhamad; Syaqhina Nifa Hidayat; Ghita Alya Ranindya; Risfaiza Fathinka Latanya; Chandrika Maulida Hutami (International Journal Labs, 2025)
Pregnancy is often accompanied by significant psychological challenges, including increased risk of depression, anxiety, and stress, which can adversely affect both maternal and fetal outcomes. Non-pharmacological interventions such as Pilates have been proposed as effective strategies to improve mental health during pregnancy. This systematic review and meta-analysis aimed to evaluate the effectiveness of Pilates in reducing depression, anxiety, and stress among pregnant women. Quality assessment was performed using the Cochrane RoB 2.0 tool and meta-analysis was conducted using RevMan 5.4. This study assessed mental illness symptom including depression, anxiety, and stress to evaluate the effect of pilates over periods of 8 to 12 weeks. A search across seven databases identified five articles for analysis, with five low-risk. The meta-analysis shows that pilates interventions, compared to control or usual care, significantly reduced symptoms of depression (SMD: -2.70; 95% CI: -3.27 to -2.13), anxiety (SMD: -1.19; 95% CI: -1.58 to -0.80), and stress (SMD: -6.62; 95% CI: -8.11 to -5.13), all with p<0.00001. High heterogeneity was observed for each outcome (I²=75–89%). This result suggest that pilates can be good exercise to reduce mental illness in pregnant women. Pilates is an effective, safe, and accessible intervention for reducing depression, anxiety, and stress in pregnant women, with additional physical and obstetric benefits. Future research should focus on standardizing intervention protocols, expanding to more diverse and high-risk populations, and assessing long-term outcomes to further inform clinical practice.